PARADOKS OTONOMI KHUSUS ACEH DALAM PELAYANAN KESEHATAN PUBLIK MELALUI DINAMIKA KEBIJAKAN DAN IMPLEMENTASI PEMERINTAHAN DAERAH - Andre Al-Qusayrie; Tiara Humaira (NIHAYAH: Journal of Islamic Studies, 2026)
The special autonomy granted to Aceh provides significant authority and financial resources to its regional government, particularly in the delivery of public services such as healthcare. This autonomy is expected to enhance the quality, accessibility, and equity of public health services through decentralized decision-making and locally responsive policies. This study aims to analyze the dynamics of health policy and its implementation within the framework of Aceh's special autonomy, focusing on the paradoxes between the distribution of authority, budget allocation, and the results of public health services. The research specifically investigates how regional governance practices impact the effectiveness and equity of healthcare services in the province. Using a qualitative descriptive-analytical approach, the study employs policy study methods and a case study of Aceh. Data were collected from in-depth interviews with key stakeholders, such as health officials, health facility managers, members of the Aceh Regional Parliament, and health workers. Secondary data, including regulatory documents and regional health reports, were also analyzed. The findings reveal significant paradoxes within the health sector, where, despite substantial authority and budget support, the delivery of health services remains inefficient. Disparities between urban and rural areas persist, budget utilization lacks clear prioritization, and institutional capacity remains weak. Political dynamics and administrative challenges further hinder effective policy implementation. The study concludes that the effectiveness of public health services in Aceh is determined more by governance dynamics than by the availability of authority or financial resources alone. Strengthening institutional capacity, improving coordination, and adopting equity-focused policies are crucial for achieving sustainable improvements in public health services.